The government party and the opposition party: distinction of identities and political debate in the press of Rio de Janeiro (1837) (Ágora Journal, 2022)
This paper, we will demonstrate the political scene of the year 1837 in Rio de Janeiro. We understand that this rivalries context between government and opposition deputies, outlining their ideas through newspapers, gradually created a favorable environment for the emergence of political parties in the Empire. Thus, this article sought to determine the main themes that led the groups to conflict that year, until the abdication of Diogo Antônio Feijó. To analyze the sources, we used the study of methodology of political languages, with a theoretical basis in the conception of political culture.